Didactical framework for the simulation of computer performance analysis - La Red Martínez, David Luis (2017)
Fil: La Red Martínez, David Luis. Universidad Nacional del Nordeste. Facultad de Ciencias Naturales y Exactas y Naturales y Agrimensura; Argentina.